2021
DOI: 10.3389/fnut.2021.689055
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol-Rich Aronia melanocarpa Juice Consumption Affects LINE-1 DNA Methylation in Peripheral Blood Leukocytes in Dyslipidemic Women

Abstract: Cardiovascular disease (CVD) is associated with alterations in DNA methylation and polyunsaturated fatty acid (PUFA) profile, both modulated by dietary polyphenols. The present parallel, placebo-controlled study (part of the original clinical study registered as NCT02800967 at www.clinicaltrials.gov) aimed to determine the impact of 4-week daily consumption of polyphenol-rich Aronia melanocarpa juice (AMJ) treatment on Long Interspersed Nucleotide Element-1 (LINE-1) methylation in peripheral blood leukocytes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…This has been supported by several pilot studies and a meta-analysis for Aronia berries, which showed that regular consumption of Aronia juice can reduce the incidence of urinary tract infection and the use of antibiotics of elderly residents of nursing homes [50] and decrease blood pressure and total cholesterol levels to show potential cardioprotective effects [60][61][62][63][64][65]. In addition, Aronia berries were found to show immunomodulating activity [55,56,59], and they exhibited synergistic effects with elderberries for their inhibitory potency against β-coronavirus-1 (HCoV-OC43) [53].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This has been supported by several pilot studies and a meta-analysis for Aronia berries, which showed that regular consumption of Aronia juice can reduce the incidence of urinary tract infection and the use of antibiotics of elderly residents of nursing homes [50] and decrease blood pressure and total cholesterol levels to show potential cardioprotective effects [60][61][62][63][64][65]. In addition, Aronia berries were found to show immunomodulating activity [55,56,59], and they exhibited synergistic effects with elderberries for their inhibitory potency against β-coronavirus-1 (HCoV-OC43) [53].…”
Section: Discussionmentioning
confidence: 82%
“…The results showed that consumption of Aronia berries decreased LINE-1 methylation levels and the arachidonic acid/eicosapentaenoic acid ratio. Cardiovascular disease is associated with alterations in DNA methylation and PUFA profile, and thus this clinical trial indicates some potential cardioprotective effects of the habitual consumption of Aronia juice [60].…”
Section: Potential Benefits To the Prevention And Treatment Of Cardio...mentioning
confidence: 76%
“…A study from 2021 assessed the effect of chokeberry juice consumption on the metalation of long interspersed nucleotide element 1 (LINE-1) in peripherial blood leukocytes in women with cardiovascular risk factors, including those who were overweight and dyslipidemic [150]. LINE-1 is considered to be an important factor in assessing the global methylation of the genome in the body.…”
Section: Impact Of Chokeberry On Lipid Profilementioning
confidence: 99%
“…Among the polyphenols influencing DNA methylation are catechin, epicatechin, (−)-epigallocatechin-3-O-gallate (EGCG), quercetin, and genistein [154,155]. Stojković et al (2021) showed a decrease in LINE-1 methylation after 4 weeks of consuming chokeberry juice in women, and thus, as the authors emphasized, chokeberry may have had a cardioprotective effect [150].…”
Section: Impact Of Chokeberry On Lipid Profilementioning
confidence: 99%
“…In recent years, plant polyphenols have been associated with various beneficial effects on human health because of their antidiabetic, cardiovascular [ 4 ], neuroprotective and antihypertensive [ 5 ] actions. Some evidence of their protective and therapeutic effects on diseases that are closely connected to immune response such as inflammatory diseases, allergic occurrences, or autoimmune diseases has been reported [ 6 ].…”
Section: Introductionmentioning
confidence: 99%